Urinary concentration of endocrine-disrupting phthalates and breast cancer risk in Indian women: A case-control study with a focus on mutations in phthalate-responsive genes. (August 2022) - Mukherjee Das, Ankan; Gogia, Ajay; Garg, Manoj; Elaiyaraja, Arun; Arambam, Priyadarshini; Mathur, Sandeep; Babu-Rajendran, Ramaswamy; Deo, S.V.S.; Kumar, Lalit; Das, Bhudev C.; Janardhanan, Rajiv
Abstract: Background: Phthalates are known endocrine-disrupting chemicals used indiscriminately as constituents in consumer products including food processing, and packaging, cosmetics, personal care and household items. Although, few studies have assessed the risk of breast cancer on exposure to phthalates, their association with breast cancer risk in Indian women have not yet been evaluated. Methods: We conducted a case-control study involving 171 participants. Urinary concentrations of six phthalate dieters; DMP (Dimethyl phthalate), DEP (Diethyl phthalate), DBP (Dibutyl phthalate), BBP (benzyl butyl phthalate), DEHP (Di-2-ethyl-hexyl phthalate), DINOP (Di-n-octyl phthalate) were estimated by GC-MS and geometric means were calculated. Univariate and multivariable logistic regression was performed to assess breast cancer risk on exposure to phthalates. Genes responsive to phthalates were identified through literature search and matched with NGS data, and gene-enrichment analysis was performed. Results: Significant associations were observed between urinary phthalate concentrations and increased risk of breast cancer for di-butyl phthalate (OR=1.5, 95% CI; 1.06, 2.11, p = 0.002) and di-2-ethyl-hexyl phthalate (>median vs ≤ median; OR=2.97, 95% CI; 1.18, 7.47, p = 0.005) in multivariable analyses. We also found several phthalate-responsive gene mutations in paired breast tumor tissues, which include PTPRD (76.19%), AR (42.86%), CYP1A1 (42.86%), CYP19A1 (23.81%), AHRR (19.05%), PIK3CA (19.05%), CYP1B1 (9.52%), RB1 (9.52%) and MMP9 (9.52%). Gene-enrichment analysis revealed that these genes form a major part of ER/PR, PPAR and HIF-1α-TGF-β signaling cascades involved in breast cancer Conclusion: Although the sample size is small, in this first case-control study from India, DBP and DEHP were found to be associated with increased risk of invasive breast cancer and tumor tissues revealed mutations in several phthalate-responsive genes. It is, therefore suggested that human biomonitoring in India and larger studies evaluating the early life genetic and epigenetic alterations on phthalates exposure are required to establish their role in breast carcinogenesis. Graphical Abstract: ga1 Highlights: Phthalate esters were estimated in urine samples of Indian women. Phthalates detected in pre-diagnostic and pre-treatment urine samples of breast cancer patients. DBP and DEHP found associated with increased risk of breast cancer in Indian women. Damaging mutations in several known phthalate-responsive/target genes were identified. Novel single nucleotide variants in phthalate-responsive/target genes are detected.